Determinan Kepatuhan Wajib Pajak: Digitalisasi, Kesadaran, dan Pengetahuan Perpajakan - Annisa Fatimatu Zahro; Nera Marinda Machdar (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to analyze the influence of tax digitalization, taxpayer awareness, and tax knowledge on the level of taxpayer compliance in Indonesia. This study is based on the low level of tax compliance even though tax revenues have increased significantly thanks to digitalization. The method used is a literature review, with secondary data analysis from various relevant sources. The results of the study indicate that tax digitalization contributes positively to taxpayer compliance, facilitating reporting and reducing fraud. In addition, tax awareness and knowledge have also been shown to increase compliance, where taxpayers who understand their obligations tend to be more compliant. This study concludes that in order to increase taxpayer compliance, further efforts are needed to increase tax awareness and knowledge, as well as optimally utilize digital technology. The implications of the results of this study are important for tax policy in Indonesia to support increased state revenues.